2021
DOI: 10.3348/kjr.2020.1362
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Novel Three-Dimensional Magnetic Resonance Fingerprinting of the Prostate Gland: Phantom and Clinical Studies

Abstract: Objective To evaluate the feasibility of a new three-dimensional (3D) MR fingerprinting (MRF) technique for the prostate gland by conducting phantom and clinical studies. Materials and Methods The new 3D MRF technique used in this study enables quick data acquisition and has a high resolution. For the phantom study, the MRF T1 and T2 values in an in-house phantom were compared with those of gold-standard mapping methods using linear regression analysis. For the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Currently, a 2D acquisition is used, and each slice acquisition can take up to 50 seconds. Three-dimensional prostate MRF acquisition would accelerate acquisition and also produce higher-resolution images and is currently being investigated with initial promising results 101–103 …”
Section: Current Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a 2D acquisition is used, and each slice acquisition can take up to 50 seconds. Three-dimensional prostate MRF acquisition would accelerate acquisition and also produce higher-resolution images and is currently being investigated with initial promising results 101–103 …”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…Three-dimensional prostate MRF acquisition would accelerate acquisition and also produce higher-resolution images and is currently being investigated with initial promising results. [101][102][103]…”
Section: Prostate Imagingmentioning
confidence: 99%
“…MRF T1 and ADC values were found to be complementary for malignant lesion staging, whereas there was an overlap in MRF T2 values between different lesion types [ 64 ]. Han et al recently used 3D MRF in phantoms and 90 patients with suspected prostate cancer [ 65 ]. Findings were consistent with the results from 2D MRF trials for prostate cancer, and the image acquisition protocol provided faster coverage of the entire prostate gland (4 min rather than 7–8 min).…”
Section: Magnetic Resonance Fingerprinting For Imaging Cancermentioning
confidence: 99%
“…4 In the MR fingerprinting technique, T1 mapping and T2 mapping can be obtained by postprocessing the data that had been acquired while changing the flip angle and echo time for about 5 minutes. 5 In this issue of JMRI, the article "Value of T2 mapping for prostate cancer detection and classification" showed that prostate cancer and surrounding tissues were well distinguished in the T2 mapping image. The average T2 relaxation time of prostate cancer was 85 msec in the peripheral zone (PZ) and 75 msec in the transition zone (TZ), and authors suggested 92 msec as a cut-off value for diagnosing prostate cancer.…”
mentioning
confidence: 99%
“…Nowadays, T2 mapping can be done within 5 minutes by using methods such as parallel imaging and model‐based reconstruction method which gives more than 15 different TE values 4 . In the MR fingerprinting technique, T1 mapping and T2 mapping can be obtained by postprocessing the data that had been acquired while changing the flip angle and echo time for about 5 minutes 5 …”
mentioning
confidence: 99%